Metabolismo do cromo orgânico e seu efeito sobre a fauna ruminal de cordeiros - Rocha, José Francisco Xavier da (2013)
The use of micro minerals in farm animals is widely studied in order to enhance the production and the reproductive performance of these animals. However, considering small ruminants, information about minerals metabolism is scant. Thus, the aim of this study was to evaluate the metabolism of chrome and its effect in the ruminal fauna of lambs. A total of four male lambs 4 months old and with a mean weight of 28 Kg were used in this study. Animals were maintained in metabolic cages during a period time of 20 days (i.e., 15 days of adaptation period and 5 days of experimental period). The mineral was administered through infusion of one milligram of yeast rich in chrome (Sacharomices cerevisae), in the rumen during whole study period. It were evaluated the dry matter (DM) rate of the animals diet and feces in order to estimate the ingestion, digestibility and fecal production. Blood, feces and urine samples were collected every 24 hours during the experiment to determine the chrome excretion. The ruminal fluid was collected at different time points, i.e., day 0, +3 and +5 after begin of the experiment. No alterations were observed in the chrome excretion in the urine, at the same time, it was not detected the mineral (i.e., chrome) in the plasma, being this excretion basically fecal. Animals from treated group presented a higher excretion of chrome than those belong to the control group at day 0 and +3. The utilization of organic chrome allowed an increase in the ingestion of dry matter (DM) at day 0 (P < 0.05). The fecal production of DM in the supplemented group was higher than those observed in the control group in the days 1, 2, 3 and 4 (P ˂ 0.05). It was not detected difference in the digestibility, DM ingestion and ruminal fauna during the study. In conclusion, lambs supplemented with organic chrome did not absorb this mineral, consequently, no alteration was observed in the ruminal fauna.